2000
DOI: 10.1118/1.599030
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and verification of Virtual Wedge in a three‐dimensional radiotherapy planning system

Abstract: Virtual Wedge (VW) is a Siemens treatment modality which generates wedge-shaped dose distributions by moving a collimator jaw from closed to open at a constant speed while varying the dose rate in every 2 mm jaw position. In this work, the implementation and verification of VW in a radiotherapy treatment planning (RTP) system is presented. The VW implementation models the dose delivered by VW using the Siemens monitor units (MU) analytic formalism which determines the number of MU required to generate a wedge-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Thus, within the MU fraction model, the WF for the virtual wedge is unity. As is the case for the EDW wedge factors, investigators [102][103][104] have found that the WF is unity for most cases with the exception of the 60…”
Section: B1ii Physical Wedges a Number Of Investigatorsmentioning
confidence: 99%
“…Thus, within the MU fraction model, the WF for the virtual wedge is unity. As is the case for the EDW wedge factors, investigators [102][103][104] have found that the WF is unity for most cases with the exception of the 60…”
Section: B1ii Physical Wedges a Number Of Investigatorsmentioning
confidence: 99%
“…In Table 1, 1VW and 2VW indicate that the wedge orientation is formed by making y 1 or y 2 dynamic jaws. However, similar to the Varian EDW, Moued ( 11 ) and Miften ( 12 ) point out there may be a difference of up to 6% in the toe region on larger fields and larger wedge angles. This may be caused by overestimation by the VM model of the dose in the toe region for these field and wedge combinations.…”
Section: Resultsmentioning
confidence: 60%
“…These effects are larger for large wedge angles and large field sizes compared with other setups. ( 12 ) …”
Section: Resultsmentioning
confidence: 99%
“…All * Electronic address: dalmeida@ffclrp.usp.br the absorbance measurements [15][16][17] were done with the visible spectrophotometric technique. The results are compared with the ones reported using Monte Carlo [1], film [4], ionization chamber [3,4] and diodes [1]. Similar measurements, made with an ionization chamber of 0.016 cm 3 , are also reported here.…”
Section: Introductionmentioning
confidence: 60%
“…There are several papers reporting the results of wedge beam profile measurements from physical, virtual and dynamic filters, using different dosimeters such as diode [1,2], ionization chamber [3][4][5], chemical dosimeter [6][7][8], film [2,4] and numerical methods that use Monte Carlo calculation codes [1,9]. In this work the Fricke Xylenol Gel (FXG) was used to measure the beam profiles of physical wedge filters used in 6 MV photons clinical beams.…”
Section: Introductionmentioning
confidence: 99%